Establishing RNAi in a Non-Model Organism: The Antarctic Nematode Panagrolaimus sp. DAW1. - Anna C Seybold; David A Wharton; Michael A S Thorne; Craig J Marshall (PLoS ONE, 2016)
The Antarctic nematode Panagrolaimus sp. DAW1 is one of the only organisms known to survive extensive intracellular freezing throughout its tissues. Although the physiological mechanisms of this extreme adaptation are partly understood, the molecular mechanisms remain largely unknown. RNAi is a method that allows the examination of gene function in a direct, targeted manner, by knocking out specific mRNAs and revealing the effects on the phenotype. In this study we have explored the viability of RNAi in Panagrolaimus sp. DAW1. In the first trial, nematodes were fed E. coli expressing Panagrolaimus sp. DAW1 dsRNA of the embryonic lethal genes rps-2 and dhc, and the blister gene duox. Pd-rps-2(RNAi)-treated nematodes showed a significant decrease in larval hatching. However, qPCR showed no significant decrease in the amount of rps-2 mRNA in Pd-rps-2(RNAi)-treated animals. Several soaking protocols for dsRNA uptake were investigated using the fluorescent dye FITC. Desiccation-enhanced soaking showed the strongest uptake of FITC and resulted in a significant and consistent decrease of mRNA levels of two of the four tested genes (rps-2 and tps-2a), suggesting effective uptake of dsRNA-containing solution by the nematode. These findings suggest that RNAi by desiccation-enhanced soaking is viable in Panagrolaimus sp. DAW1 and provide the first functional genomic approach to investigate freezing tolerance in this non-model organism. RNAi, in conjunction with qPCR, can be used to screen for candidate genes involved in intracellular freezing tolerance in Panagrolaimus sp. DAW1.